Urgensi Bahasa Isyarat dalam Pendidikan Formal sebagai Media Komunikasi dan Transmisi Informasi Penyandang Disabilitas Rungu dan Wicara - Norifumi Aisyah Muhammad Amin; Farid Pribadi (Universitas Negeri Makassar, 2022)
Communication and transmission of information have a major role in human life. The presence of barriers caused by limited information and sign language skills can create gaps and communication failures. As a result, people with disabilities and speech often experience lag in their environment. This paper uses qualitative research methods, with literature study techniques. Overall, the integration of sign language into the curriculum will enable the development of a deaf culture. Applying sign language in a formal educational environment benefits both individuals with disabilities and individuals without disabilities.